2012
DOI: 10.1002/jcb.24128
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive guidance molecule B (RGMB) plays negative roles in breast cancer by coordinating BMP signaling

Abstract: Repulsive guidance molecules (RGMs) coordinate axon formation and iron homestasis. These molecules are also known as co-receptors of bone morphogenetic proteins (BMPs). However, the role played by RGMs in breast cancer remains unclear. The present study investigated the impact of RGMB on functions of breast cancer cells and corresponding mechanisms. RGMB was knocked down in breast cancer cells by way of an anti-RGMB ribozyme transgene. Knockdown of RGMB resulted in enhanced capacities of proliferation, adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Alterations, following RGMb knockdown, were observed in the regulation of c-myc, caspase-3, SNAIL, TWIST, FAK and paxillin. This study also implicated RGMb knockdown to contribute to the Smad-dependent pathway, enhancing levels of activated Smad 1 and 3 in untreated cells, with greater responses seen following BMP-7 treatment and a switching to Smad 1 activation following inhibition of Smad 3, whereas phosphorylation of JNK, ILP and TAK was inhibited following RGMb knockdown suggesting suppression of the Smad-independent pathway (22).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Alterations, following RGMb knockdown, were observed in the regulation of c-myc, caspase-3, SNAIL, TWIST, FAK and paxillin. This study also implicated RGMb knockdown to contribute to the Smad-dependent pathway, enhancing levels of activated Smad 1 and 3 in untreated cells, with greater responses seen following BMP-7 treatment and a switching to Smad 1 activation following inhibition of Smad 3, whereas phosphorylation of JNK, ILP and TAK was inhibited following RGMb knockdown suggesting suppression of the Smad-independent pathway (22).…”
Section: Discussionmentioning
confidence: 93%
“…Further work explored the impact of targeting RGMb in breast cancer cell lines in vitro. This study demonstrated a potential role for RGMb in breast cancer proliferation, matrix-adhesion and migration where targeting this molecule enhanced these aggressive traits and implicated links with Smad-dependent and Smad-independent pathways (22). Similarly, RGMb appears to play a role in prostate cancer progression.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations